2013
DOI: 10.2527/jas.2012-5081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytase supplementation in mature horses fed alfalfa hay and pelleted concentrate diets

Abstract: An experiment was conducted to study P digestibility in mature horses because of the growing environmental concerns regarding P runoff and previous equine research focused mostly on young and growing animals or used ponies as a model. Phytase supplementation of swine and poultry diets can result in greater phytate-P digestibility, leading to a decreased need for inorganic P supplementation and a decrease in P excreted to the environment; this, however, has not been demonstrated in the horse. Six mature Arabian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…The observed digestibilities of Ca not differing between the diets agreed with the literature values [2,7,18,35]. Van Doorn et al [18] have reported that high amounts of P and phytate P may decrease Ca digestibility.…”
Section: Intake Fecal Excretion and Digestibility Of Calcium And Magsupporting
confidence: 88%
See 2 more Smart Citations
“…The observed digestibilities of Ca not differing between the diets agreed with the literature values [2,7,18,35]. Van Doorn et al [18] have reported that high amounts of P and phytate P may decrease Ca digestibility.…”
Section: Intake Fecal Excretion and Digestibility Of Calcium And Magsupporting
confidence: 88%
“…The larger excretion of Mg compared with its intake in all diets, except those including the complete feed, explains, the poor Mg digestibility in these diets. The digestibility of Mg has been reported to be largely varying, and negative values have also been reported [2,7,18,35], as in the present study. Because Ca and Mg are excreted in large quantities in urine [9,40], the observed digestibilities here may be underestimated.…”
Section: Intake Fecal Excretion and Digestibility Of Calcium And Magsupporting
confidence: 80%
See 1 more Smart Citation
“…For calcium analysis, urine was acidified with 12 M HCl (EMD Chemicals) at a rate of 20 μl/ml of urine to ensure all precipitate was in solution (O'Connor‐Robison & Nielsen, 2006). Faecal and hay samples were oven‐dried for 24‐hr (Thelco; Precision Scientific), ground to 1 mm particles (Cyclotec 1093 Sample Mill; Foss) and microwave digested (MARS5; CEM Corp.) with nitric acid (70% trace‐metal grade; Fisher Scientific) in duplicate as described by Shaw, Rozeboom, Hill, Booren, and Link (2002) and Lavin et al (2013). Calcium concentrations in hay, faeces, and urine were determined by atomic absorption spectroscopy (AA‐7000; Shimadzu) with each urine sample and microwave digest run in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary P requirements for horses are calculated using estimates of true digestibility of 35% or 45% depending on the form of P in the diet (NRC, 2007). However, in the equine literature true P digestibility values have been reported to range from −10% to 79% (Kichura, Hintz, & Schryver, 1983; Lavin et al, 2013), but there is no consensus on why this large variation occurs. In cattle, true P digestibility is 80% (NRC, 2001).…”
Section: Introductionmentioning
confidence: 99%